The Influence Of Education And Training Programs On Employee Achievement In Republic Of Indonesia Public Radio Broadcasting Institution Medan - Raymond Fransiscus; Lapiti Gokmatua Sagala; Maduma Sari Sagala (Jurnal Ekonomi, 2024)
Education and training are carried out by private companies and government agencies with the aim of creating a potential workforce and improving employee skills.This research was conducted at LPP RRI Medan with a sample of 30 people and the sampling technique used was the saturated sampling method. Data sources are primary data and secondary data. Data collection methods are observation, interviews, questionnaires and documentation. Analysis of the data used is multiple linear regression analysis, t test, F test and coefficient of determination.From the results of the study with a partial test, the educational variable has a positive and significant effect on employee performance, it can be seen with tcount = 2.863> t table = 2.051 and sig 0.005 <0.05. The training variable has a positive and significant effect on employee performance, it can be seen from tcount = 14.120> ttable = 2.051 and sig 0.000 <0.05. Simultaneously, the variables of education and concentration have a positive and significant effect on employee performance, it can be seen from Fcount = 469205 > Ftable = 3.145 and sig 0.000 <0.05. The coefficient of determination is obtained at 78.4%. It can be interpreted that 78.4% of employee performance is influenced by education and training programs, the rest is influenced by other variables